2014
DOI: 10.1002/clc.22313
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Predictors of Mortality Among Octogenarians and Older With ST‐Segment Elevation Myocardial Infarction Treated With Primary Coronary Angioplasty

Abstract: Background: Elderly patients are at high risk of mortality when they present with ST-elevation myocardial infarction (STEMI). However, few data exist about prognostic factors in this sub-group when treated with primary percutaneous coronary intervention (pPCI). Hypothesis: To assess outcome and predictors of mortality among patients aged >80 years treated with pPCI. Methods: We evaluated 139 consecutive patients (age 85.1 ± 3.9 years, 43.2% males) who underwent pPCI for STEMI. Results: Male patients were young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 17 publications
3
18
1
Order By: Relevance
“…showed that female age ≥85 years, female sex, anterior MI, cardiogenic shock and unsuccessful reperfusion were the predictors of mortality in 30 days . Consistently, older age, heart failure and shock were shown as independent predictors of mortality in 30 days after STEMI …”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…showed that female age ≥85 years, female sex, anterior MI, cardiogenic shock and unsuccessful reperfusion were the predictors of mortality in 30 days . Consistently, older age, heart failure and shock were shown as independent predictors of mortality in 30 days after STEMI …”
Section: Discussionmentioning
confidence: 62%
“…Advances in mortality and morbidity with invasive therapy were clearly shown in this population . Predictors of long‐term mortality in octogenarian patients, who has undergone primary PCI after acute STEMI, were studied in some other studies . However, risk factors for in‐hospital mortality were underrepresented.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Beside age of the patient, many other variables have been proven to be an independent predictor of unfavorable outcome in the elderly undergoing PCI. Reduced cardiac function with left ventricular ejection fraction (LVEF) lower than 40%, Killip class of 3 or worse, cardiogenic shock, and hypotension with systolic blood pressure (SBP) lower than 100 mmHg have all been identified as independent predictors of an increased risk of 1-year mortality [43] . Also, the activity of daily living (ADL) of old age patients after PCI can be used to predict mortality.…”
Section: Pci Adverse Eventsmentioning
confidence: 99%
“…As it was discussed above, the coronary lesions in the elderly tend to be more complex and extensive which may render them suitable only for plain old balloon angioplasty (POBA) due to a failure of stent delivery, or inability to stent lesions in distal or small diameter vessels [43] . On the other hand, stenting technology has revolutionized during the last era.…”
Section: Type Of Stentmentioning
confidence: 99%